Experimental of Quadcopter Trajectory Tracking Control Based ROS - Pipit Angraeni; Muhammad Nursyam Rizal; Hilda Khoirunnisa; Theo Kristian (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Quadcopters have become popular in various fields, such as environmental surveying, mapping, monitoring, and rescue operations. However, controlling the trajectory of a quadcopter remains a major challenge. In this article, we propose an adaptive PID control approach based on ROS (Robot Operating System) to control the motion of a quadcopter. We tested the proposed control model on a simulation platform and on a physical quadcopter system. Simulation results demonstrate better control capabilities than conventional PID control approaches. Additionally, the proposed control system successfully controlled the quadcopter accurately on multiple different trajectories in the physical system. We demonstrate the effectiveness of the adaptive PID control approach in tracking the quadcopter's trajectory with greater accuracy. Experiment results show that the proposed control system is highly suitable for more advanced quadcopter applications and allows for more accurate navigation. Quadcopter telah menjadi populer dalam aplikasi berbagai bidang, seperti survei lingkungan, pemetaan, pemantauan dan penyelamatan. Namun, pengendalian trajektori quadcopter masih menjadi tantangan besar. Dalam artikel ini, kami mengusulkan pendekatan kontrol pid adaptif berbasis ROS (Robot Operating System) untuk mengendalikan gerakan quadcopter. Kami menguji model kontrol yang diusulkan pada platform simulasi dan pada sistem fisik quadcopter. Hasil simulasi menunjukkan kemampuan kontrol yang lebih baik dari pendekatan kontrol pid konvensional. Selain itu, sistem kontrol yang diusulkan berhasil mengendalikan quadcopter pada beberapa lintasan berbeda secara akurat pada sistem fisik. Kami menunjukkan efektivitas pendekatan kontrol pid adaptif dalam melacak lintasan quadcopter dengan akurasi yang lebih baik. Hasil eksperimen menunjukkan bahwa sistem kontrol yang diusulkan sangat mampu digunakan pada aplikasi quadcopter yang lebih canggih dan memungkinkan navigasi yang lebih akurat.